Wide-Field Imaging with NAVILAS Laser System - A. N. Kulikov; D. S. Maltsev; M. A. Burnasheva; V. V. Volkov; V. F. Danilichev; R. L. Troyanovskiy (Oftalʹmologiâ)
Purpose: to study the potential of wide-field imaging with NAVILAS laser system.Material and methods. In this study we included patients diagnosed with indirect ophthalmoscopy as having one of the follows: diabetic retinopathy (6 eyes), central retinal vein occlusion (5 eyes), choroidal melanoma (3 eyes), rhegmatogenous retinal detachment (4 eyes), and peripheral chorioretinal degeneration (10 eyes). Using NAVILAS 532 laser system and a wide-field contact lens (HR Wide Field (VOLK)) a wide-field central image and a panoramic (consisted of 4 to 6 images) images were obtained in all patients. Fundus images were evaluated according to their diagnostic value versus indirect ophthalmoscopy and wideness of the viewing angle versus standard color fundus photography (55°). In each patient within a single session were obtained: 1) a central fundus image and 2) panoramic image (4-field and in dynamic mode). In a subgroup of patients with central retinal vein occlusion and lattice retinal degeneration, we studied the ability of simultaneous laser photocoagulation wide-field imaging.Results. A single field images obtained with NAVILAS allows to visualize up to 130.3 ± 9.6° of the eye fundus while four-field and dynamic acquisition up to 150.1 ± 8.9° and 171.3 ± 17.0°, respectively. Representative findings of diabetic retinopathy, central retinal vein occlusion, choroidal melanoma, rhegmatogenous retinal detachment, and peripheral lattice degeneration were identified in all cases. Insufficient visualization was found for “snail track” degeneration because the subtle retina and choroid changes were hardly seen on the low magnified image. In 4 patients with lattice retinal degeneration and 3 patients with central retinal vein occlusion within a single session, both wide-field imaging and laser photocoagulation were performed. Surgical goals were achieved in all cases.Conclusion. Wide-field imaging with NAVILAS laser system demonstrated high potential in the documentation of the most widely spread eye fundus disease the and represents an adequate alternative for wide-field fundus cameras. Aside from wide-field imaging this approach also allows for simultaneous laser photocoagulation in entire eye fundus including far peripheral retina.